2013
DOI: 10.1136/bmjqs-2013-001888
|View full text |Cite
|
Sign up to set email alerts
|

A Dutch regional trauma registry: quality check of the registered data

Abstract: The reliability of injury coding in a regional trauma registry was 'substantial' and the reliability of the ISS and survival status was 'almost perfect'. The format and design of this study were feasible and could be used to investigate the quality of (trauma) registries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 16 publications
4
20
0
Order By: Relevance
“…All data related to the care and diagnostics were registered by the healthcare providers themselves during the consultation. This registration of diagnosis and treatment activities in the medical record was comparable to those of other medical records that are considered to be valid and reliable (Visscher et al 2012, Olthof et al 2013.…”
Section: Validity and Reliabilitysupporting
confidence: 68%
“…All data related to the care and diagnostics were registered by the healthcare providers themselves during the consultation. This registration of diagnosis and treatment activities in the medical record was comparable to those of other medical records that are considered to be valid and reliable (Visscher et al 2012, Olthof et al 2013.…”
Section: Validity and Reliabilitysupporting
confidence: 68%
“…The current findings are in concordance with previously published work on variability of trauma registry data and reflect the ongoing discussion about the need for improved data accuracy [ 14 , 17 , 18 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…In another study recoding 120 cases in the Queensland Trauma Registry, on average 39% of the codes used by any two coders for each of the injured persons were identical [ 20 ]. In the Netherlands, two independent studies demonstrated substantial accuracy on the number of AIS codes in regional trauma registries [ 17 , 18 ]. In a subgroup analysis of severely injured patients (ISS ≥ 16), however, accuracy was fair (intraclass correlation coefficient = 0.33) [ 17 ], and the authors concluded that discrepancies in injury coding are more likely to occur in this population.…”
Section: Discussionmentioning
confidence: 99%
“…[21] The reliability of injury coding was found to be substantial and the reliability of the ISS almost perfect. [21,22] Only severely injured patients (ISS > 15) were included in this study, because an ISS of 16 is predictive of 10% mortality and defines major trauma based on anatomic injury. [23] Within the group severely injured patients a cut-off score of 25 is used, because a rapid increase in fatalities is seen when de ISS exceeds the value of 25.…”
Section: Instrumentsmentioning
confidence: 99%
“…Serious intracranial injury (AIS>3) was present in 52% of the cases. The median ISS was 21 (interquartile range [17][18][19][20][21][22][23][24][25][26][27], and 86% of the participants had received ICU treatment. Participant characteristics are presented in table 1.…”
Section: Participants' Characteristicsmentioning
confidence: 99%